What’s happening with thinking - Wan Yusoff, Wan Mazwati (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
Immersing myself into reading hundreds of articles and books made me realised the importance of defining concepts correctly because these concepts set the frameworks within which ideas are constructed into practices. Wrong concepts will result in wrong ideas and wrong practices. Since man is at the centre of education, therefore I was taught the definition of man from the perspective of the Quran and Sunnah. It is only logical to look in the Quran for the meaning of “human” since we believe that Allah is the Creator of human, therefore Allah knows best what and who human is, thus the right place to look to understand the essence of human and to be human is in the Quran and in the lifestyle of Prophet Muhammad. Concisely we answer the question of “What is human?” as a creation of Allah who is endowed with body, mind and soul. Human is responsible to ensure that all of these dimensions are developed to produce an individual who is well-balanced physically, psychologically, intellectually and spiritually. All endeavour of education at all level must ensure that the human is developed holistically. From here my lamentation of the state of education in the Garden of Knowledge and Virtue begins.